Sensitized photooxidation of triclosan pesticide. A kinetic study in presence of vitamin B2 - Reynoso, Agustina (2021)
Kinetic and mechanistic aspects of Riboflavin (Rf, vitamin B2)-sensitized photochemical degradation of Triclosan (TCS) have been studied by time-resolved and stationary techniques. TCS is a broadly-used biocide, also employed in a series of industrial products as a multifunctional additive. Rf, in the presence of light and oxygen, generates singlet molecular oxygen (O2(1Δg)) and superoxide radical anion (O2[rad]–). Results indicate that TCS quenches the triplet excited state of Rf (3Rf*), O2(1Δg), and O2[rad]–. The reactive rate constant for the interaction TCS-O2(1Δg) is 62-faster in alkaline medium with respect to pH 7. Photosensitized degradation of TCS by Rf was much faster than for phenol, a model pollutant, in similar conditions of pH. Kinetic analysis indicated that the reaction of TCS with 3Rf* and/or O2[rad]– is the prevailing oxidative route. Based on the environmental importance of the TCS, the products were determined by UHPLC-MS / MS analysis.